Industry 4.0 : Digital transformation replicability in manufacturing - Geroldová, Lucie (2018)
This thesis outlines a replicable roadmap for manufacturing companies who aim to implement Industry 4.0 technologies into their operations. Based on a thorough literature review, a case study and qualitative expert interviews, this paper identifies key pillars, drivers, and trends of the fourth industrial revolution and their impact on the business, providing specific examples. The author suggests the starting point of a successful digital transformation should be a clear digitalization strategy, followed by an overview of specific goals the manufacturer aims to achieve. This enables the company to identify relevant metrics and detailed KPIs to ensure the company is on track with the digitalization initiatives. Furthermore, different aspects of the company’s business model will be impacted by the digital transformation and the manufacturers must be prepared to face Industry 4.0-specific challenges.